Systemic inflammation with enhanced brain activation contributes to more severe delay in postoperative ileus. Issue 8 (27th May 2013) - van Bree, S. H. W.; Cailotto, C.; Di Giovangiulio, M.; Jansen, E.; van der Vliet, J.; Costes, L.; Depoortere, I.; Gomez‐Pinilla, P. J.; Matteoli, G.; Boeckxstaens, G. E. E.
Abstract: Background: The severity of postoperative ileus (POI) has been reported to result from decreased contractility of the muscularis inversely related to the number of infiltrating leukocytes. However, we previously observed that the severity of POI is independent of the number of infiltrating leukocytes, indicating that different mechanisms must be involved. Here, we hypothesize that the degree of tissue damage in response to intestinal handling determines the upregulation of local cytokine production and correlates with the severity of POI. Methods: Intestinal transit, the inflammatory response, I‐FABP (marker for tissue damage) levels and brain activation were determined after different intensities of intestinal handling. Key Results: Intense handling induced a more pronounced ileus compared with gentle intestinal manipulation (IM). No difference in leukocytic infiltrates in the handled and non‐handled parts of the gut was observed between the two intensities of intestinal handling. However, intense handling resulted in significantly more tissue damage and was accompanied by a systemic inflammation with increased plasma levels of pro‐inflammatory cytokines. In addition, intense but not gentle handling triggered enhanced c‐Fos expression in the nucleus of the solitary tract (NTS) and area postrema (AP). In patients, plasma levels of I‐FABP and inflammatory cytokines were significantly higher after open compared with laparoscopic surgery, and were associated with more severe POI. Conclusions & Inferences: Not the influx of leukocytes, rather the manipulation‐induced damage and subsequent inflammatory response determine the severity of POI. The release of tissue damage mediators and pro‐inflammatory cytokines into the systemic circulation most likely contribute to the impaired motility of non‐manipulated intestine.